(untitled) (Eurasian Journal of Philology Science and Education, 2018)
This article is devoted to study individually-authorial world perception features, reflected on the material of T.Iztileuov’s fiction works. As it is generally known, the world view in the artistic text is created by language means, here it reflects the individual world view in the writer’s consciousness and it is realized in the selection of elements of artistic work maintenance, language, because the question is about literary work, where language serves as a means of creation of the artistic world. It is considered, how the originality of the national picture of the world, basic features of national mentality of the Kazakh people, and also individually-authorial world view of the writer are reflected in the works of T.Iztileuov. Also language units, performing the characterizing duty, thus answering the disclosure of the image of the hero are studied in it